FINANCIAL EFFICIENCY OF BPRS (SHARIA RURAL BANKS) ACROSS PROVINCES IN INDONESIA - Hidayatun Khasanah; Mochammad Yana Aditya (Jurnal Dinamika Ekonomi Syariah, 2025)
The disparity in BPRS financial efficiency between provinces is an academic challenge that requires data-based solutions and in-depth analysis. This study aims to measure the level of BPRS financial efficiency in various provinces in Indonesia in 2021-2024. The type of research applied is quantitative research with the DEA (Data Envelopment Analysis) approach, which is used to measure the level of BPRS financial efficiency in accumulation per province. Based on the results of the Data Envelopment Analysis (DEA) analysis with three models (CRS, VRS Output, and VRS Input), there are variations in the level of efficiency among provinces in Indonesia. In the CRS model, 5 provinces have high efficiency, 13 provinces are moderately efficient, 5 provinces are lowly efficient, and 1 province is inefficient. The VRS Output model shows an increase, namely 10 provinces with high efficiency, 10 provinces with moderate efficiency, 4 provinces with low efficiency, and 1 province is inefficient. Meanwhile, the VRS Input model produces 11 provinces with high efficiency, 10 provinces with moderate efficiency, and 4 provinces with low efficiency. Overall, the majority of provinces are in the moderate efficiency category. It was found that the province that consistently showed high efficiency for 4 years was DKI Jakarta. Meanwhile, provinces with low and inefficient efficiency (Bangka Belitung, Banten, Bali, East Kalimantan, Central Sulawesi, and West Sulawesi) require improvements in resource allocation to improve their performance.